2007
DOI: 10.1021/jo701592x
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the HOMO and LUMO Energy Levels of Organic Chromophores for Dye Sensitized Solar Cells

Abstract: A series of organic chromophores have been synthesized in order to approach optimal energy level composition in the TiO2-dye-iodide/triiodide system in the dye-sensitized solar cells. HOMO and LUMO energy level tuning is achieved by varying the conjugation between the triphenylamine donor and the cyanoacetic acid acceptor. This is supported by spectral and electrochemical experiments and TDDFT calculations. These results show that energetic tuning of the chromophores was successful and fulfilled the thermodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
436
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 594 publications
(455 citation statements)
references
References 26 publications
14
436
1
4
Order By: Relevance
“…Tuning the HOMO and LUMO energy levels of organic dyes for DSSCs is a good method for improving the performance of DSSCs [17]. Tian et al [10,18] reported that the excited-state oxidation potentials of TH301 and TH305 are À1.17 and À1.28 V, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Tuning the HOMO and LUMO energy levels of organic dyes for DSSCs is a good method for improving the performance of DSSCs [17]. Tian et al [10,18] reported that the excited-state oxidation potentials of TH301 and TH305 are À1.17 and À1.28 V, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among the donor moieties, N, N-dimethylaniline group, 9,10 coumarins, [11][12][13][14][15][16][17] tetrahydroquinolines, 18,19 pyrrolidine, 20 carbazoles, 21 diphenylamine, 22 triphenylamine, [23][24][25][26] etc have been widely used for the dye synthesis. A linker moiety is a spacer added between the donor and acceptor moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 7 was treated with nBuLi, followed by addition of anhydrous DMF, to give trialdehyde 8 in 86 % yield. [20] Scheme 2 illustrates the synthetic approach to G0-4-2. The key component, the "masked" AB 2 building block 10, bears one unprotected thiophene group for further modification and two thiophene groups with hexyl chains.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%